Impacts of the surrounding land use land cover changes on Suba Sabeta forest, Ethiopia, and associated community perception - Belete Z. Deyessa; Alemayehu N. Emana (Sustainable Environment, 2024)
Impacts of the surrounding land use land cover changes on Suba Sabeta Forest over the past three decades from 1990 to 2020 and associated community perception were assessed employing an integrated approach of Landsat images analysis, household survey, key informants interview and focus group discussion. The study involved collection of both quantitative and qualitative data which were analyzed using descriptive statistics. The results revealed that forests and shrub declined from 9,220 ha and 1335 ha to 2702 ha and 783 ha while settlement and bare land increased from 866 ha and 273 ha to 5,589 ha and 3,978 ha, respectively. Cultivated land increased from 12,162 ha in 1990 to 14,329 ha in 2005 and then declined to 10,811 ha by 2020. Respondents’ responses also indicated a drastic decline in the forest cover related to fuel wood collection (81.6%), settlement (13.8%), cutting trees for construction (3.3%) and expansion of cultivated land (1.3%). According to the respondents poverty (79.08%) and population growth (20.92%) were the underlying causes of the forest cover decline. Responses further revealed disappearance of indigenous plants (biodiversity loss) (73.2%), soil erosion (18%) and decline in agricultural production (8.8%) related to the decline in forest cover. Thus, protection of the remnant forest, reforestation and developing renewable alternative energy sources might help to mitigate further decline in Suba Sebeta Forest cover and associated impacts.